A CMOS 6–10 GHz impulse radio UWB transmitter based on gated oscillator with switching pulse shaper. (July 2018) - Park, Yangkyu; Kwon, Ickjin
Abstract: In an impulse radio ultra-wideband (IR-UWB) system for low-power location-aware sensor networks, the output pulses must meet the FCC spectral emission mask. In addition, to increase battery life, the IR-UWB transmitter must be energy efficient. In this paper, a CMOS ultra-wideband (UWB) transmitter designed using a 0.11-μm process is presented for 6–10 GHz applications. To reduce energy consumption, the transmitter adopts a gated voltage-controlled oscillator (VCO) that directly drives 50 Ω output impedance. A gated VCO that uses a trapezoidal pulse for on/off gating of the tail current source satisfies the spectrum mask without requiring an additional pulse shaping filter. The active energy consumption is 13.4 pJ/pulse at a pulse repeating frequency (PRF) of 40 MHz. The side-lobe rejection performance is more than 30 dB.